2022
DOI: 10.1029/2022jb024432
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Anhysteretic Remanent Magnetization Carriers in Magnetofossil‐Rich Marine Sediments

Abstract: The anhysteretic remanent magnetization (ARM) is a laboratory-imparted artificial remanence that is used widely in mineral magnetic studies (Dunlop & Özdemir, 1997). An ARM is usually imparted by exposing a sample to an alternating field (AF; e.g., ∼100 mT) with a superimposed small direct current (DC; e.g., ∼50 μT) bias field. The bulk ARM is given as the sum of the ARM of each component (Egli, 2004a(Egli, , 2004bFabian & Leonhardt, 2009):where M ar is the bulk ARM imparted with a DC field H dc for a sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 114 publications
1
6
0
Order By: Relevance
“…Thus, we consider that RPI from NRM/IRM _20-40mT is carried by magnetofossils, and RPI from NRM/ IRM _70-160mT is carried mainly by partially oxidized unprotected magnetites of detrital origin. The observation that ARM little carries a coercivity component higher than 70 mT even for ARM acquired at AF of 160 mT supports the interpretation that the middle-coercivity component of the IRM decomposition is mainly of detrital origin and magnetofossils little contribute to this component (Zhang et al, 2022).…”
Section: Relative Paleointensitysupporting
confidence: 66%
See 2 more Smart Citations
“…Thus, we consider that RPI from NRM/IRM _20-40mT is carried by magnetofossils, and RPI from NRM/ IRM _70-160mT is carried mainly by partially oxidized unprotected magnetites of detrital origin. The observation that ARM little carries a coercivity component higher than 70 mT even for ARM acquired at AF of 160 mT supports the interpretation that the middle-coercivity component of the IRM decomposition is mainly of detrital origin and magnetofossils little contribute to this component (Zhang et al, 2022).…”
Section: Relative Paleointensitysupporting
confidence: 66%
“…The lower RPI recording efficiency of magnetofossils when normalized by ARM can be partly explained by that higher ARM acquisition efficiency of magnetofossils causes underestimation of RPI (Li et al., 2022; Yamazaki, 2008; Zhang et al., 2022). This study confirmed that lower RPI recording efficiency of magnetofossils occurs also for RPI normalized by IRM, which was previously suggested from calculating RPI separately from different coercivity ranges like this study (Li et al., 2022) or inverse correlation with k ARM /SIRM (Inoue et al., 2021; Sakuramoto et al., 2017; Yamazaki et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our FORC‐PCA results show that biogenic magnetite was abundant during the MH and LH at higher sea level (Figure 7a). χ ARM /SIRM has recently been used to determine the relative abundance of magnetofossils in sediments (Wang, Xu, et al., 2022; Yamazaki et al., 2020; Zhang et al., 2022), which showed that the relative abundance of magnetofossils increased gradually during the last deglaciation and reached a stable state during the MH and LH (Figures 7a and 7b). The relative variation in magnetofossil abundance in the Qiongdongnan basin was consistent with that in the northwest sub‐basin of the SCS (Figure 7c) (Wang, Xu, et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Saturation isothermal remanent magnetization (SIRM) was measured using an AGICO JR‐6A spinner magnetometer after applying a 1 T field using a pulse coil. χ ARM /SIRM was obtained to reflect the abundance of fine magnetite particles, also as a proxy for the proportion of magnetofossils in magnetic mineral assemblages (Egli, 2004b; Yamazaki et al., 2013; Zhang et al., 2022). All paleomagnetic measurements of the 87 samples were conducted at the Institute of Geology and Geophysics, Chinese Academy of Sciences (IGGCAS).…”
Section: Samples and Methodsmentioning
confidence: 99%